2019
DOI: 10.31234/osf.io/42j7v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consequences of Attributing Discrimination to Implicit vs. Explicit Bias

Abstract: Implicit bias has garnered considerable public attention, with a number of behaviors (e.g., police shootings) attributed to it. Here, we present the results of 4 studies and an internal meta-analysis that examine how people reason about discrimination based on whether it was attributed to the implicit or explicit attitudes of the perpetrators. Participants’ perceptions of perpetrator accountability, support for punishment, level of concern about the bias, and support for various efforts to reduce it (e.g., edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Bias if often framed as implicit or unconscious, yet it is unsure whether this framing is legitimate 35,36 . Meanwhile, framing bias as implicit can have severe negative consequences as it reduces people's motivation, accountability and responsibility regarding bias reduction 37,38 . Also, it could pave the way for ignorance, 39–41 and undermine perceptions of the severity of discrimination 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Bias if often framed as implicit or unconscious, yet it is unsure whether this framing is legitimate 35,36 . Meanwhile, framing bias as implicit can have severe negative consequences as it reduces people's motivation, accountability and responsibility regarding bias reduction 37,38 . Also, it could pave the way for ignorance, 39–41 and undermine perceptions of the severity of discrimination 42 .…”
Section: Discussionmentioning
confidence: 99%
“…2 Further, research exploring lay understandings of implicit (automatic, often without awareness) and explicit biases (intentional, with awareness, see Gawronski & Bodenhausen, 2006; Greenwald & Banaji, 1995) offers insights into the implications of believing that prejudice is intentional or unintentional. This research has found that attributing prejudice to implicit biases is associated with perceiving perpetrators as less accountable and deserving of less punishment compared to attributing prejudice to explicit bias (Daumeyer et al., 2019). Indeed, one of the most basic inferences people make is perceived intentionality of an act (Malle & Holbrook, 2012) and perceived intentionality can shape how one responds, including moral judgements of harm and responsibility (Ames & Fiske, 2013, 2015; Malle, 2004; Weiner, 1995).…”
Section: Lay Theories Of Prejudicementioning
confidence: 99%
“…Popular media may also contribute to increasing public awareness by communicating the scientific evidence for biased weighting and biased interpretation to nonacademic audiences. Because describing bias as unconscious can lead people to feel less accountable for biased actions (Daumeyer et al, 2019;Payne et al, 2010), discussions of implicit bias should emphasize the responsibility of individuals and organizations to create policies and procedures to prevent expressions of implicit bias in individual behavior. To avoid implying that bias only exists at the level of individuals, these discussions should also contextualize the issue of implicit bias at the individual level in a broader understanding of systemic and historical bias (see Bonam, et al, 2019;Salter et al, 2018).…”
Section: Raising Awarenessmentioning
confidence: 99%